Pengaruh Brand Image Terhadap Keputusan Pembelian Toyota Agya Di PT Auto2000 Asia Afrika Bandung - Sugesti , Hesti; Afadhillah , Aulia Syifa; Anggraeni , Angga Dewi; Abdillahsk , Haiqal (Jurnal Ekonomi Bisnis, Manajemen dan Akuntansi, 2024)
This study aims to determine whether the Toyota Agya car in auto2000 provides a purchase decision for customers, based on brand image and purchase decision. This research uses quantitative research. This research is used to prove the relationship between several variables. This research uses a descriptive approach with 99 respondents who are service providers at auto2000 in the city of Bandung. The variables in this study are brand image (X) and purchasing decisions (Y). The data collection method used is a questionnaire. The data analysis method used is descriptive analysis and simple linear regression analysis. Data processing tools use SPSS for windows version 25.0. Based on the results of simple linear regression analysis, brand image has a significant and positive effect on purchasing decisions. So this explains that brand image has a positive influence on determining the Toyota Agya purchasing decision process at PT.Auto2000 Asia Afrika Bandung.